The Family and Safety of the Hospitalized Patient: An Integrative Literature Review - Tânia Sofia Pereira Correia; Maria Manuela Ferreira Pereira da Silva Martins; Fernando Fausto Margalho Barroso (Karger Publishers, 2020)
Framework: Considering that the current data on health care safety remain alarming, there is an overwhelming urge for the ongoing study of this topic and for recommendations and differentiated strategies which aim to promote health and which prove effective. Some recommendations have been taken into consideration, such as patient-centered care, and consequently the need for greater involvement of patient and family in this process. However, we have identified arguments for and against the involvement of family in the care process, and consequently a greater or lesser openness towards hospital visits. Objective: What are the implications of the presence of family for the safety of hospitalized patients? What does the science say about these implications? Methods: We conducted an integrative literature review by referring to the Web of Science, CINAHL, Medline, and Scopus databases, according to the recommendations of the Joanna Briggs Institute for scoping review. Results: We found 115 articles. After selection, 13 articles were included in this review. There were 6 qualitative studies, 5 quantitative studies, and 2 literature reviews. Data were grouped according to: the perspective of patients and their families, the health professionals' perspective, and statistical evidence. Conclusion: Families take efforts to protect the safety of hospitalized patients but feel unprepared; a lack of follow-up was reported. Some health professionals claim that the presence of the family can increase the risks for patient safety and the fear of an increased workload. The evidence of the presence of the family and its link to the safety of the hospitalized patient demonstrated that this relationship is not yet well understood. There were limited findings about this in the current literature. Relevance to Clinical Practice: Structured interventions about family integration in ensuring the safety of hospitalized patients may have the potential to contribute to the safety of health care.